Impact of Frontline Demonstrations on Mustard in Sahibganj District of Jharkhand - Jha, Amrit Kumar; Mehta, Birendra Kumar; Kumari, Maya; Chatterjee, Kaushik (Indian Journal of Extension Education, 2021)
Cluster Frontline Demonstrations (CFLDs) on mustard were conducted during 2016-17 to 2019-20 in ten villages of Sahibganj district of Jharkhand covering 641 farmers and 250 ha area to evaluate the impact of scientific production techniques on productivity and profitability. Performance of mustard varieties Pusa Mahek and Pusa Mustard 26 in 641 locations along with improved cultivation practices were evaluated during demonstrations. It was observed that the yield of mustard in CFLD under irrigated conditions ranged from 10.82 q to 12.36 q ha-1 whereas in Farmer’s Practice (FP) it ranged between 7.3 to 8.5 q ha-1. The per cent increase in yield was recorded in the range of 45.06 to 48.21. The extension gap and technological index ranged between 3.52 to 3.86 q ha-1 and 27.29 to 36.35 per cent, respectively. The trend of technology gap reflected the farmer’s cooperation in carrying out demonstrations with encouraging results in subsequent years. Maximum gross return (Rs 51,912 ha-1) and net return (Rs 25,912 ha-1) was fetched during four observation years. The benefit cost ratio varied from 1.71 to 2.05 under demonstration, while it was 1.39 to 1.70 under farmer’s practice. Therefore, the results clearly indicate that the use of improved variety and package of practice with scientific intervention under cluster frontline demonstration programme contribute to increase the productivity and profitability of mustard.
Keywords: Extension gap; Mustard; yield; Cluster frontline demonstrations; Technology index; Economics